Immediate Implant Placement of a Single Central Incisor Using a CAD/CAM Crown‐Root Form Technique: Provisional to Final Restoration. Issue 1 (27th September 2016) - Vafiadis, Dean; Goldstein, Gary; Garber, David; Lambrakos, Anthony; Kowalski, Bj
Abstract: Objective: Preserving soft and hard tissues after extraction and implant placement is crucial for anterior esthetics. This technique will show how the information gathered from a cone‐beam computed tomography (CBCT) scan of the maxillary left central incisor and an intra‐oral digital impression can be merged to fabricate a CAD/CAM crown‐root matrix to be used as an immediate provisional restoration that mimics the natural anatomy. Clinical Considerations: Due to trauma, a left central incisor appeared to be fractured and was scheduled for extraction and implant placement. The crown‐root configuration captured by the CBCT scan was merged with the digital files from an intra‐oral digital impression. A CAD/CAM crown‐root matrix was fabricated. Because the matrix shell was fabricated with the exact anatomy of the natural tooth, it replicated the position and three dimensional anatomy of the soft and hard tissue. It was connected to the implant with a customized provisional abutment. A digital impression of a coded healing abutment was made to fabricate the final implant abutment and final restoration. Throughout the treatment time and 36 months after completion, the thickness of tissue, emergence profile, and adjacent papilla was analyzed by clinical evaluation and photography and seemed to be maintained. Conclusion: The use of a pre‐operative intra‐oral digital scan of the clinical crown‐root architecture and the CBCT scan of the bone/root anatomy, can be used together to fabricate a CAD/CAM crown‐root form provisional matrix. This digital design helps in the preservation of the 3D tissue topography, as well as the final restoration. Clinical Significance: The preservation of soft and hard tissue after extraction and implant placement has always been paramount for ideal anterior implant esthetics. Using the information from digital files from CBCT scans and intra‐oral scans may help the clinician identify critical anatomical features that can be replicated in the provisional and final CAD/CAM restoration. (J Esthet Restor Dent 29:13–21, 2017)